(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Genetic rescue – the deliberate augmentation of gene flow between isolated small populations to counteract inbreeding depression and restore adaptive potential – has emerged as one of the most evidence-supported and rapidly deployed conservation interventions for populations at immediate genetic extinction risk, yet its application remains controversial due to concerns about outbreeding depression, loss of local adaptation, and the ethical dimensions of manipulating wild population genetics. This review and meta-analysis synthesises 48 published genetic rescue experiments and natural gene flow events in vertebrate and invertebrate taxa, quantifying the magnitude of fitness benefits, the frequency of outbreeding depression, and the genomic predictors of rescue outcome. Across 48 case studies (n = 2,842 individual fitness measurements from rescue recipients), the mean fitness benefit of genetic rescue was +42.4 +- 18.4% in the first generation post-introduction (F1), declining to +28.4 +- 12.4% by F3 as inbreeding depression was resolved and additive genetic variance was partially depleted. Outbreeding depression was detected in only 4 of 48 cases (8.3%), all involving crosses between populations diverged by > 2 million years or involving distinct ecotypes with documented local adaptation. The strongest predictors of rescue success were: pre-rescue inbreeding coefficient (F(ind) > 0.20: stronger rescue effect; β = +0.48; p < 0.001), effective population size of donor population (Ne(donor) > 100: higher fitness gain; β = +0.38; p < 0.001), and genetic divergence between donor and recipient (FST < 0.20: lower outbreeding risk; β = -0.42; p < 0.001). A Decision Support Tool (DST) for genetic rescue planning, integrating these three predictors into a categorical recommendation framework, correctly predicted rescue outcome in 84.4% of case studies. These results support wider adoption of genetic rescue as a conservation tool for highly inbred small populations and provide an evidence-based decision framework for species-specific rescue planning.